Ecotoxicological Impact of Agro-Industry on Streams From a South American Basin: Amphibian Tadpoles as Indicators of Environmental Health - Cuzziol Boccioni, Ana Paula (2025)
This study aimed to evaluate complex contamination due to anthropic activities related to urban, industrial and agricultural activities in four streams of Entre Ríos-Argentina (Las Conchas, LC; Espinillo, ES; Crespo, CR; Las Tunas, LT), being the first one the main water sources of subtropical riparian conservation reserve “Parque Escolar Rural Enrique Berduc” (PEREB). Physicochemical and bacteriological parameters and pesticide residues were studied on sediment and water samples. Toxicity bioassays on Rhinella arenarum tadpoles were performed to analyze ecotoxicological effects. Sediment from LC stream had the highest glyphosate concentration recorded in South American (5002 μg/kg). Bioassays showed lethality (100%) in undiluted CR and LT treatments. Sublethal effects included thyrotoxicosis, neurotoxicity, and genotoxicity on treated ES, CR, and LT tadpoles. These findings highlight the alarming environmental degradation threatening “One health,” emphasizing the need for sustainable practices and severe control by science and government to protect and ecological restore freshwater sources.